2006
DOI: 10.1007/s11117-006-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive Operators à la Aumann-Shapley on Spaces of Functions on D-Lattices

Abstract: Let L be a σ-complete D-lattice and BV the AL-space of all realvalued, null in zero, functions on L of bounded variation. We prove the existence of a continuous Aumann-Shapley operator φ on the closed subspace of BV generated by powers of nonatomic σ-additive positive modular measures on L. The integral representation of φ on a class of functions that correspond to measure games is also exhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The two approaches are known to be equivalent, according to [12,Theorem 1.3.4], so that in particular lattice-ordered effect algebras and D-lattices are two ways of considering the same thing. We shall privilege the concepts of D-poset and of D-lattice, in order to be consistent with the previous paper [6].…”
Section: Modular Measures On D-latticesmentioning
confidence: 99%
See 3 more Smart Citations
“…The two approaches are known to be equivalent, according to [12,Theorem 1.3.4], so that in particular lattice-ordered effect algebras and D-lattices are two ways of considering the same thing. We shall privilege the concepts of D-poset and of D-lattice, in order to be consistent with the previous paper [6].…”
Section: Modular Measures On D-latticesmentioning
confidence: 99%
“…Here and in the previous paper [6], a generalization of that kind is accomplished in case the original algebra of subsets C is replaced by a σ-complete lattice-ordered effect algebra L, thus weakening the assumptions of [2] and [10] in a remarkable way. In particular, in [6] it is proved the existence of a value φ on pNA, the subspace of BV spanned by powers of non-atomic σ-additive positive modular measures on L; furthermore, an integral representation of φ on a class of measure games is obtained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we have given a Jordan type decomposition theorem for a locally bounded real-valued measure m defined on L, followed by various properties in the context of functions m + , m − and |m| (cf. [3]). In Section 4, using the notion of an atom of a real-valued measure m [24,25], we have showed that the range of a locally bounded real-valued σ-additive, non-atomic function m on a D-lattice L is an interval (−m − (1), m + (1)); characterizations of nonatomicity of m are established and used in obtaining this result (cf.…”
mentioning
confidence: 99%